High-fat/high-carbohydrate-diet short- and middle-term effects on gerbil adrenal zona fasciculata histology. (April 2022) - Bellahreche, Zineb; Semiane, Nesrine; Mallek, Aicha; Dahmani, Yasmina
Highlights: Gerbil adrenal gland histological features. Use of gray level co-occurrence matrix texture and fractal dimension to examine the zona fasciculata. Gerbillus gerbillus as a model of central obesity. Adrenal gland adaptation to high-fat/high-carbohydrate diet. Abstract: The adrenals synthesize many hormones involved in the regulation and maintenance of homeostasis. To understand the pathophysiological changes during the development of obesity, a histological study of the adrenal was performed in gerbils receiving a high-fat/high-carbohydrate-diet (HFC) for 8 or 12 weeks. Compared to the controls, the HFC diet increased body weight. Our results reveal significant weight and structural changes in the HFC group's adrenal glands (confirmed by gray level co-occurrence matrix texture and fractal analysis), disorganization of zona fasciculata (8 weeks) and hyperplasia and peri-capillary fibrosis (12 weeks). In conclusion, these results show that an HFC induces time-dependent structural lesions of the adrenals in gerbils, which could be a sign of chronic adaptation of these glands.